Tracking synthetic microdebris contamination in a highly urbanized estuary through crabs as sentinel species: An ecological trait-based approach - Truchet, Daniela María (2022)
Synthetic microdebris (particles of <5 mm) are a worldwide concern because they can affect the community structure of the aquatic ecosystems, organisms, and even food webs. For the biomonitoring of synthetic microdebris (especially microplastics, MPs), mainly benthic invertebrates are used, but crabs have been less studied in the literature. We studied the synthetic microdebris contamination in water, sediments, and three representative intertidal crabs (Neohelice granulata, Cyrtograpsus angulatus and Leptuca uruguayensis) with different lifestyles from the Bahía Blanca estuary, Argentina. The results obtained show the presence of cotton-polyamide (PA), polyethylene (PE), and polyethylene terephthalate (PET) in surface waters. In sediments, we identified cellulose modified (CE), polyester (PES), polyethylene (PE), and alkyd resin, while in crabs, cotton-PA and CE were the predominant ones. The MPs abundance ranged from 8 to 68 items L−1 in surface water, from 971 to 2840 items Kg−1 in sediments, and from 0 to 2.58 items g−1 ww for the three species of crabs. Besides, paint sheets ranged from 0 to 17 in the total samples, with Cr, Mo, Ti, Pb, Cu, Al, S, Ba and Fe on their surface. There were significant differences between the microdebris abundances in the abiotic matrices but not among crabs species. The ecological traits of the different crabs helped to understand the accumulation of synthetic microdebris, an important characteristic when determining the choice of a good biomonitor.